THE ROLE OF TEACHERS IN DEVELOPING STUDENTS’ CHARACTER OF HONESTY AND HARD WORK AT SDN 7 CAKRANEGARA - Muslehudin; Didi Wahyudin; Fauji; Lalu Sumardi (Academic Journal Research, 2026)
Objective: This study aims to analyze the role of teachers in developing students' character, particularly honesty and hard work, through a character and discipline guidance program at SDN 7 Cakranegara. Method: This research uses an ex post facto method with a descriptive qualitative approach involving interviews, observations, and documentation. Results: The findings show that teachers play a significant role through exemplary behavior, routine moral habituation, motivational strategies, and participatory learning methods. Although the program positively shapes students' honesty and work ethic, challenges remain, especially students’ diverse backgrounds and low learning motivation. Novelty: Strengthening instructional strategies, parental involvement, and continuous character-building activities proved essential in internalizing honesty and hard work among students.